Contact sensitization in patients with chronic venous insufficiency and the impact of the disease duration on the risk of occurence of contact sensitization - Vujanović, Ljuba; Jovanović, Marina; Matić, Milan; Jakovljević, Sanja; Golušin, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Development of allergic contact dermatitis as a complication of treatment of chronic venous insufficiency (CVI) is well known. The aim of this study was to determine the incidence and risk of eczematous contact sensitization in patients with CVI, as well as the correlation between disease duration and contact sensitization. Methods. The study involved 266 subjects examined during three-year-period who were divided into two groups: the study group included patients with CVI referred for allergy testing due to suspected contact dermatitis, and the control group included the ones without CVI patch tested for suspected contact dermatitis. The severity of CVI was assessed by Clinical Etiology-Anatomy-Pathophysiology (CEAP) classification. Thereafter, each patient underwent patch testing. Results. The incidence of contact sensitization among patients with CVI was 49.3%. In these patients, the incidence of contact sensitization to the European standard battery of allergens was 31.55%; to the battery specific for CVI it was 28.45%. Patients with CVI had a 2.45-fold higher risk for developing contact sensitization to two or more allergens, and a 3.69-fold higher risk for developing contact sensitization to five or more allergens compared to those without CVI. The prevalence of contact sensitization in patients with CVI was not significantly different from those without CVI. There was a positive correlation between the incidence of contact sensitization and the duration of the disease. Conclusion. Patients with CVI had no statistically significantly distinct contact sensitization prevalence and had 2.45 and 3.69 times higher risk to manifest contact sensitization to two and more allergens and five and more allergens, respectively, than patients with no CVI. The positive correlation between frequency of contact sensitization and disease duration was found.
Keywords: dermatitis, contact; incidence; risk assessment; venous insufficiency